Centrality of agriculture to India's economic development - Majumdar, N.A. (2006)
Indian agriculture faces a far more complex set of problems in the new millennium. They are however of a new genre. Our vision of agricultural growth in the new millennium is that it should be a means of achieving the broader objectives of food security, employment-led growth and poverty reduction. - Reproduced.
Keywords: Agriculture - India; Economic and social development - India; Economic and social development